ANALISIS YURIDIS PENGATURAN PEMISAHAN BERKAS PERKARA (SPLITSING) BERDASARKAN KITAB UNDANG-UNDANG HUKUM ACARA PIDANA - Annisa, Fitri; Indra, Mexsasai; ', Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
In the case of the settlement of criminal cases there are arrangements that do not provide legal certainty that leads to multiple interpretations leading to misappropriation. In the case of the formulation of a criminal case becomes one of confusion among law enforcers in particular the separation of the file of the case or Splitsing. Separation of a case file or Splitsing is regulated in Article 142 of the Criminal Procedure Code, namely "In the case of the public prosecutor receiving a case file containing several crimes committed by several suspects not included in Article 141 of the Criminal Procedure Code, the prosecutor may prosecute each Defendants separately. "The arrangement of the split file or Splitsing has not supported the evidentiary system within the criminal justice system. Splitsing arrangements are not strict and do not provide legal certainty so as to cause adverse impacts in particular law enforcement in the case of the compilation of criminal case files of perpetrators of criminal acts for subsequent prosecution. The purpose of this thesis writing is: First, to know whether the arrangement of split file or splitsing case has supported the principle of proof in the criminal justice system, Secondly, to find out the ideal arrangement of split case file or splitsing in the judicial system. This type of research is normative legal research or can be called also research doctrinal law. From the research results of the problem there are two main points that are concluded, First, the arrangement of the separation of the file of the case or the explicit Splitsing is to provide legal certainty in law enforcement and support the evidentiary system in the criminal justice system. Secondly, Article 142 of the Criminal Procedure Code does not provide explicit legal certainty in particular the separation of case files or Splitsing, it is necessary to stipulate explicitly about the splitsing case separation provisions to ensure legal certainty as well as the evidentiary system within the criminal justice system.Keywords: Separation arrangement of a case file or Splitsing-System of Evidence-The Criminal Justice System